Home » Questions » Unexperienced [ Ask a new question ]

Use elimination -4x - 5y -z = 18-2x - 5y -2z = 12-2x + 5y +2z =4

Use elimination -4x - 5y -z = 18-2x - 5y -2z = 12-2x + 5y +2z =4

Asked by: Guest | Views: 24
Total answers/comments: 1
Guest [Entry]

equation 2 and 3-2x - 5y - 2z = 12-2x + 5y + 2z = 4 to eliminate y and z--------------------------4x = 16 x = -4using equation 1 and 2[-4x - 5y - z = 18] × -1 4x + 5y + z = - 18-2x - 5y - 2z = 12------------------------ 2x - z = -62(-4) - z = -6 -8 - z = -6 - z = - 6 + 8 - z = 2 z = -2Solve y. Subs x and z to equation 1-4(-4) - 5y - (-2) = 1816 - 5y + 2 = 18-5y = 18 - 16 - 2-5y = 0 y = 0To check in equation -2x + 5y + 2z = 4 -2(-4) + 5(0) + 2(-2) = 4 8 - 4 = 4 4 = 4